2001
DOI: 10.1104/pp.127.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining the Arabidopsis Genome Reveals Fifteen 14-3-3 Genes. Expression Is Demonstrated for Two out of Five Novel Genes

Abstract: In plants, 14-3-3 proteins are key regulators of primary metabolism and membrane transport. Although the current dogma states that 14-3-3 isoforms are not very specific with regard to target proteins, recent data suggest that the specificity may be high. Therefore, identification and characterization of all 14-3-3 (GF14) isoforms in the model plant Arabidopsis are important. Using the information now available from The Arabidopsis Information Resource, we found three new GF14 genes. The potential expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
164
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 20 publications
7
164
2
1
Order By: Relevance
“…For example, a total of 15 14-3-3 genes, called General Regulatory Factor1 to GRF15, were identified in Arabidopsis (Arabidopsis thaliana), whereas only eight 14-3-3 genes were identified in the rice (Oryza sativa) genome (DeLille et al, 2001;Rosenquist et al, 2001;Chen et al, 2006;Yao et al, 2007). In the recently sequenced genome of soybean (Glycine max; Schmutz et al, 2010), 18 14-3-3 genes were identified and named Soybean G-box Factor 14-3-3a (SGF14a) to SGF14r (Li and Dhaubhadel, 2011).…”
mentioning
confidence: 99%
“…For example, a total of 15 14-3-3 genes, called General Regulatory Factor1 to GRF15, were identified in Arabidopsis (Arabidopsis thaliana), whereas only eight 14-3-3 genes were identified in the rice (Oryza sativa) genome (DeLille et al, 2001;Rosenquist et al, 2001;Chen et al, 2006;Yao et al, 2007). In the recently sequenced genome of soybean (Glycine max; Schmutz et al, 2010), 18 14-3-3 genes were identified and named Soybean G-box Factor 14-3-3a (SGF14a) to SGF14r (Li and Dhaubhadel, 2011).…”
mentioning
confidence: 99%
“…The intron positions in the 14-3-3 gene family are also conserved. Pp14-3-3b gene encoding non-ε 14-3-3 protein contains six introns, just like the members in pear (Wu et al 2013), apple (Velasco et al 2010), and also Arabidopsis (Wu et al 1997;Rosenquist et al 2001). Plant 14-3-3 genes were differentially and specifically expressed in various tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple 14-3-3 genes exist in each plant. For example, fifteen 14-3-3 genes were identified in Arabidopsis (Rosenquist et al 2001). In this research, the isolation and characterization of the pear Pp14-3-3b gene and its expression pattern during fruit development are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human 14-3-3 h was shown to interact with PDK1 and reduced the activity via binding to Ser-241, a site corresponding to Thr-211 in AtPDK1 [22]. Thus, in the search for AtPDK1 interaction partners we tested the effect on its autophosphorylation by incubating AtPDK1 with 12 of the fifteen different Arabidopsis 14-3-3 isoforms identified [29]. For nine of the 12 isoforms tested, phosphorylation of AtPDK1 was enhanced, whereas one isoform, 14-3-3 o, significantly suppressed phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although all the 14-3-3 isoforms in A. thaliana show high sequence similarities, phylogenetic trees comparing amino acid sequences of 14-3-3 isoforms in A. thaliana as well as in other plants show that o is branched out from the other isoforms at an early stage [23], which may agree with this isoform having a distinct function. Most 14-3-3 isoforms are ubiquitously expressed in plants and 14-3-3 o is found in both roots and shoots in A. thaliana, but is less abundant compared to the other 14-3-3 isoforms [29]. Attempts to identify a 14-3-3 binding site in the AtPDK1 enzyme have so far been unsuccessful.…”
Section: Discussionmentioning
confidence: 99%